New Media in Old Cities: The Emergence of the New Collective - Cristina Ampatzidou; Ania Molenda (Footprint)
This paper takes a look at the relationship between informational space and territory. It questions the common dichotomy that positions virtual space in opposition to physical space. It focuses on the different roles modern urban actors play in defining a new understanding of space as an inseparable composition of both the virtual and the physical realm. On the individual level, it looks at the emergence of a new type of citizen whose ludic attitude dynamically adapts the course of his responses to the virtual, real-time inputs that influence his presence in the physical environment. On the collective level, it analyses unintended, swarm-like synchronisations, and the role new media play in redefining the urban commons.